Accumulated Effect of Intra-Seasonal Oscillation Convections over the Tropical Western North Pacific on the Meridional Location of Western Pacific Subtropical High - Huang, Zongci; Zhang, Wenjun; Geng, Xin; Hsu, Pang-Chi (Frontiers in Earth Science, 2020)
An extreme northward displacement of the western Pacific subtropical high (WPSH) was detected during the boreal mid-late summer (July-August) of 2018, bringing record-breaking heat waves over northern East Asia. Negative sea surface temperature (SST) anomalies in the northern India Ocean (NIO) are usually accompanied with a northward shift of the WPSH. However, no prominent NIO SST anomalies were observed during the 2018 boreal summer. It is found that this extreme northward-shifted WPSH event is largely attributed to the accumulated effect of intra-seasonal oscillation (ISO) convection anomalies over the tropical western North Pacific (WNP). The accumulated effect on the WPSH meridional location is further supported by their significant correlation (r=-0.52) based on the data since 1979. While the relationship between the NIO SST anomalies and WPSH meridional location has substantially weakened since the late 1990s, the accumulated effect of the tropical WNP ISO convections keeps playing a crucial role in modulating the WPSH meridional displacement. The active WNP ISO activities can stimulates a poleward propagating Rossby wave train, which favors a northward shift of the WPSH. Our results suggest that the accumulated effect of the tropical WNP ISO convections should be considered when predicting the WPSH during the boreal mid-late summer season.